Die römische Modelkeramik vom Magdalensberg Textband und Tafelband - Schindler-Kaudelka, Eleny (Verlag des Landesmuseums für Kärnten, 1980)
Excavations on the Magdalensberg in Carinthia, Southern Austria yielded a large number of moulded vessles of the group Norditlaica decorate, best known under the mane of the most frequent brandnames Acobeakers or Sariuscups. The research starts with the tsypological analysis following shapes, dies, decoration patterns and decorative topics. Dating results are provided following the stratigraphic contexts of the sites 100 years life and can be divided into 3 periods with a total of 7 phases secured by 40 reference contexts. Quantifications offer the base for this while . Further aspects, like production techniques, conclusions offered by workshops owner's names, different fabrics and their provenience are studied. A comprehensive catalogue of all finds from 1948 to 1979 completes the text volume, while the plates volume shows drawings, photographs and a die catalogue as well as a chronological assemblage of the examined finds.Three later papers set the Magdalensberg finds in the state of the art.SCHINDLER-KAUDELKA, E., Die römische Modelkeramik vom Magdalensberg 2. - G. PICCOTTINI (Hg.), Die Ausgrabungen auf dem Magdalensberg 1980 bis 1986. Magdalensberg-Grabungsbericht 16 (Klagenfurt 1998), 289-388.SCHINDLER-KAUDELKA, E., Cermica Norditalica decorata del Magdalensberg: problemi aperti. - G. P. BROGIOLO, G. OLCESE (Hg.), Produzione ceramica in Area padana tra il II secolo a. C. e il VII secolo d. C.: Nuove dati e prospettive di ricerca (Mantua 2000), 53-67.SCHINDLER-KAUDELKA, E., La terra sigillata norditalica decorata. A che punto siamo arrivati? - S. MENCHELLI, M. PASQUINUCCI (Hg.), Territorio e produzioni ceramiche. Paesaggi, economia e società in età Romana. Atti del convegno internazionale, Pisa 20-22 ottobre 2005 (Pisa 2006), 239-244.